A kind of lubricating grease, preparation method and use thereof

By using a combination of composite titanium-based and lithium-based grease in grease, combining anti-rust, anti-wear and antioxidants to form a stable soap fiber structure, the grease is solved at high shear, high temperature and high temperature The thinning and loss problems under wet conditions significantly improve the lubricating performance and service life.

CN116426328BActive Publication Date: 2025-02-07TOILX TIANJIN
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310611443.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-29
Publication Date
2025-02-07
Estimated Expiration
2043-05-29

AI Technical Summary

Technical Problem

Existing greases tend to become thinner and lose rapidly under high shear, high temperature and high humidity conditions, resulting in poor lubrication and short grease addition cycle, which affects production efficiency.

Method used

Using the combination of composite titanium-based grease and composite lithium-based grease, rust-proof agent, antiwear agent and antioxidant are added, and a stable soap fiber structure is formed through specific mixing and heating and stirring processes, and the dropping point of the grease is increased. and shear stability.

Benefits of technology

It significantly improves the drip point and oil film strength of the grease, enhances the ability to bind the base oil, extends the service life, avoids the problem of emulsification and thinning in high humidity conditions, and solves the short grease cycle of existing grease The problem.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides a lubricating grease, a preparation method and use thereof. The lubricating grease comprises the following raw materials in parts by weight: 75-80 parts of composite titanium-based lubricating grease, 15-20 parts of composite lithium-based lubricating grease, 2.1-6 parts of rust inhibitor, 7-16 parts of anti-wear agent, and 1-4 parts of antioxidant. The weight ratio of the composite titanium-based lubricating grease to the composite lithium-based lubricating grease is 4-5:1. The composite titanium-based lubricating grease and the composite lithium-based lubricating grease provided by the present invention act synergistically to make the soap fiber structure more stable, which is beneficial to improving the dropping point of the lubricating grease, so that the dropping point of the lubricating grease is as high as 320°C, the oil film strength is high, the shear stability of the lubricating grease is improved, and the four-ball machine load PD value of the lubricating grease is as high as 600kgf, which can enhance the binding capacity of the base oil and improve the water-resistant performance of the lubricating grease, thereby extending the service life of the lubricating grease.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of lubricating grease, and relates to a lubricating grease, a preparation method thereof, and uses thereof. Background Art

[0002] Grease is used in the friction parts of machinery to lubricate and seal. The working principle of grease is that the thickener keeps the oil in the position that needs lubrication on the mechanical equipment. When there is a load, the thickener releases the oil, thereby playing a lubricating role.

[0003] Under high shear force, high ambient temperature and high humidity, grease will quickly thin and lose, resulting in grease throwing and poor lubrication. The main reasons for the rapid thinning of grease include: 1. Under continuous high temperature, the base oil and thickener in the grease are easily oxidized to produce carbonyl molecules, and the stability of the soap fiber becomes poor. At the same time, under high shear rate, the soap fiber structure of the grease is easily destroyed, causing the grease to quickly thin and lose; 2. Under continuous high humidity conditions, the grease is easily emulsified and thinned under the action of shear force.

[0004] For example, the annealing furnace fan bearing of the galvanizing unit has a rotation speed of up to 1500rpm, a high ambient temperature of up to 150℃, and a high humidity. The existing foreign brand 1250 grease quickly thins and loses, and the grease refilling cycle is only one week, which is a very short service life and affects production efficiency.

[0005] Therefore, there is an urgent need for a lubricating grease suitable for the annealing furnace fan bearing of a galvanizing unit. Summary of the invention

[0006] In view of the above-mentioned defects or deficiencies in the prior art, the present application aims to provide a grease, a preparation method and use thereof, so as to solve at least one of the above-mentioned technical problems.

[0007] One of the purposes of the present invention is to provide a lubricating grease comprising the following raw materials in parts by weight:

[0008] 75~80 parts of composite titanium-based grease

[0009] 15~20 parts of complex lithium-based grease

[0010] Rust inhibitor 2.1~6 parts

[0011] 7-16 parts of anti-wear agent, and

[0012] 1~4 parts of antioxidant;

[0013] The weight ratio of the composite titanium-based grease to the composite lithium-based grease is 4-5:1.

[0014] Preferably, the rust inhibitor includes one or more of diketopyrrolopyrrole, dodecenylsuccinic acid, and alkenylsuccinic acid esters.

[0015] Preferably, the rust inhibitor comprises diketopyrrolopyrrole and alkenyl succinate.

[0016] Preferably, the weight ratio of the diketopyrrolopyrrole to the alkenyl succinate is 5-20:1.

[0017] Preferably, the anti-wear agent includes one or more of molybdenum disulfide, molybdenum dialkyl dithiophosphate, and molybdenum amine ester compounds.

[0018] Preferably, the antiwear agent comprises:

[0019] Molybdenum disulfide 5~10 parts

[0020] 1 to 3 parts of dialkyl dithiophosphate molybdenum, and

[0021] 1-3 parts of molybdenum amine ester compound.

[0022] Preferably, the weight ratio of the molybdenum disulfide, the molybdenum dialkyl dithiophosphate and the molybdenum amine ester compound is 4:1:1.

[0023] Preferably, the particle size of the molybdenum disulfide is 30-50 nanometers, and the friction coefficient is 0.04-0.06.

[0024] Preferably, the antioxidant comprises an amine compound and / or a phenol compound.

[0025] The second object of the present invention is to provide a method for preparing grease, which comprises the following steps: mixing the composite titanium-based grease and the composite lithium-based grease, adding the rust inhibitor, anti-wear agent and antioxidant, mixing, heating and stirring, and then grinding.

[0026] Preferably, after the composite titanium-based grease and the composite lithium-based grease are mixed, the pyrrolopyrrole dione, alkenyl succinate, molybdenum disulfide, dialkyl dithiophosphate molybdenum, molybdenum amine ester compound, amine compound and phenolic compound are added in sequence, mixed, then heated and stirred, and then ground.

[0027] Preferably, the heating temperature is 90° C. to 110° C., the stirring speed is 1000 to 1100 r / min, and the stirring time is 1.5 to 2.5 h.

[0028] Preferably, the grinding times is 3 to 5 times.

[0029] A third object of the present invention is to provide a use of the grease as described above, which is used to lubricate the bearings of the annealing furnace fan.

[0030] The beneficial effects of the present invention include:

[0031] The composite titanium-based grease and the composite lithium-based grease provided by the present invention work together to make the soap fiber structure more stable, which is conducive to improving the dropping point of the grease, so that the dropping point of the grease is as high as 320°C, the oil film strength is high, the shear stability of the grease is improved, and the four-ball machine load PD value of the grease is as high as 600kgf, which can enhance the binding ability of the base oil and improve the water-resistant performance of the grease, thereby extending the service life of the grease. Even under continuous high-humidity working conditions, it is not easy to emulsify and thin, thereby solving the problem that the overseas brand 1250 grease is easy to thin and lose quickly and has a short greasing cycle. DETAILED DESCRIPTION

[0032] In the following description, certain specific details are included to provide a comprehensive understanding of each disclosed embodiment. However, one skilled in the relevant art will recognize that the embodiments can be implemented without one or more of these specific details, but with other methods, components, materials, etc.

[0033] Unless otherwise required in this application, throughout the specification and the claims that follow, the words "including" and "comprising" should be interpreted in an open, inclusive sense, ie, "including, but not limited to."

[0034] References to "one embodiment" or "an embodiment" or "a preferred embodiment" or "certain embodiments" throughout this specification mean that the specific referenced elements, structures or features described in connection with the embodiment are included in at least one embodiment. Therefore, the phrases "in one embodiment" or "in an embodiment" or "in a preferred embodiment" or "in certain embodiments" appearing in different places throughout the specification do not necessarily all refer to the same embodiment. In addition, the specific elements, structures or features may be combined in any appropriate manner in one or more embodiments.

[0035] One of the purposes of the present invention is to provide a lubricating grease comprising the following raw materials in parts by weight:

[0036] 75~80 parts of composite titanium-based grease

[0037] 15~20 parts of complex lithium-based grease

[0038] Rust inhibitor 2.1~6 parts

[0039] 7-16 parts of anti-wear agent, and

[0040] 1~4 parts of antioxidant;

[0041] The weight ratio of the composite titanium-based grease to the composite lithium-based grease is 4-5:1.

[0042] The composite titanium-based grease has superior performance compared to the currently widely used composite potassium-based grease and composite aluminum-based grease, and its performance can be significantly improved by adding a small amount of additives. The composite titanium-based grease has good compatibility with other greases, so the composite titanium-based grease is used as the main component of the grease. In the present invention, the composite titanium-based grease is 75 parts to 80 parts, for example, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts or 80 parts.

[0043] Specifically, the composite titanium-based grease is mainly made of terephthalic acid, 12-hydroxystearic acid, an organic titanium compound and a base oil.

[0044] Wherein, the metal end of the titanium soap molecule of the composite titanium-based grease is the polar end, and the other hydrocarbon end is the non-polar end. Under appropriate conditions, the polar ends attract each other through ionic forces, and the non-polar ends attract each other through van der Waals forces. The titanium soap molecules attract each other through this ionic force and van der Waals force to form an interlaced grid skeleton, forming soap fibers. The soap fibers of the composite titanium-based grease present a cluster of three-dimensional mesh structures with wrinkles, and the base oil is locked in the wrinkles. This three-dimensional mesh structure is loose, which is conducive to the release of the base oil, but the content of hydroxyl groups is more, which will increase the activity of the soap fibers, and it is easy to be oxidized, so that the soap fiber structure is destroyed, and the oil locking ability is reduced. When subjected to high shear rate, the grease will appear to be rapidly thinned and lost. The soap fibers of the composite lithium-based grease are in the shape of a tightened rope. The tighter the soap fibers, the larger the specific surface area, and the stronger the oil locking ability. In the present invention, the composite lithium-based grease is 15 to 20 parts, for example, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts.

[0045] Specifically, the composite lithium-based grease is mainly made of hydroxy fatty acid, low molecular weight acid lithium salt and base oil.

[0046] In the present invention, the weight ratio of the composite titanium-based grease to the composite lithium-based grease is 4-5:1, for example, 4:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1, 4.6:1, 4.7:1, 4.8:1, 4.9:1 or 5:1.

[0047] In the present invention, the composite titanium-based grease and the composite lithium-based grease work together to make the soap fiber structure more stable, which is conducive to improving the dropping point of the grease, so that the dropping point of the grease is as high as 320°C, the oil film strength is high, the shear stability of the grease is improved, and the four-ball machine load PD value of the grease is as high as 600kgf, which can enhance the binding ability of the base oil and improve the anti-water spraying performance of the grease, thereby extending the service life of the grease. When the weight ratio of the composite titanium-based grease and the composite lithium-based grease is lower than 4:1, the base oil is released slowly, which will reduce the lubrication effect and anti-wear effect of the grease. When the weight ratio of the composite titanium-based grease and the composite lithium-based grease is higher than 5:1, the soap fiber is easily oxidized, the soap fiber structure is easily destroyed under high shear rate conditions, the binding ability to the base oil is poor, the oil film strength is low, the shear stability of the grease will decrease, and the anti-water spraying performance will decrease.

[0048] The rust inhibitor can form a thin film on the metal surface, so that the metal is not corroded by oxygen and water. The rust inhibitor is a polar organic compound, one end of which is a very polar group with hydrophilicity, and the other end is a non-polar hydrocarbon group with hydrophobicity. However, the amount of the rust inhibitor should not be too much, because the polar additive will damage the soap fiber structure of the lubrication system. In the present invention, the rust inhibitor is 2.1 to 6 parts, for example, 2.1 parts, 2.5 parts, 3.0 parts, 3.5 parts, 4.0 parts, 4.5 parts, 5 parts, 5.5 parts or 6 parts.

[0049] The anti-wear agent can prevent sintering, seizure, scratching and wear of the metal surface under high load conditions, and the anti-wear agent, the composite titanium-based grease and the composite lithium-based grease work synergistically to improve the anti-wear performance and extreme pressure resistance of the grease. In the present invention, the anti-wear agent is 7 to 16 parts, for example, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts or 16 parts.

[0050] When hydrocarbon molecules in the grease generate free radicals, the antioxidant can react with the free radicals to convert them into relatively stable compounds that no longer react with other hydrocarbon molecules or oxygen, thereby cutting off the oxidation reaction chain and delaying oxidation. In the present invention, the antioxidant is 1 to 4 parts, for example, 1 part, 2 parts, 3 parts or 4 parts.

[0051] In a preferred embodiment of the present invention, the rust inhibitor includes one or more of diketopyrrolopyrrole, dodecenylsuccinic acid or alkenylsuccinic acid esters.

[0052] The pyrrolopyrrole diketo has excellent migration resistance, heat stability and oil solubility, and has good rust resistance and anti-emulsification properties. The dodecenylsuccinic acid and alkenylsuccinic acid esters have good fluidity and good oil solubility and rust resistance.

[0053] In the present invention, the rust inhibitor is, for example, pyrrolopyrroledione, dodecenylsuccinic acid, alkenyl succinate, pyrrolopyrroledione and dodecenylsuccinic acid, pyrrolopyrroledione and alkenyl succinate, dodecenylsuccinic acid and alkenyl succinate, or a combination of pyrrolopyrroledione, dodecenylsuccinic acid and alkenyl succinate.

[0054] In a preferred embodiment of the present invention, the rust inhibitor comprises diketopyrrolopyrrole and alkenyl succinate.

[0055] Specifically, the anti-rust properties of the dodecenylsuccinic acid and the alkenylsuccinic acid ester are comparable, but the acid value of the alkenylsuccinic acid ester is lower than that of the dodecenylsuccinic acid. In order to prevent the soap fibers from being destroyed in an acidic environment, dionepyrrolopyrrole and alkenylsuccinic acid ester are compounded, so that the grease has excellent anti-rust and anti-emulsification properties.

[0056] Specifically, the alkenyl succinate has a strong adsorption capacity for metals and can form a highly hydrophobic protective layer, but it is easily hydrolyzed into free fatty acids, which are corrosive to metals and should not be added too much. The weight ratio of the pyrrolopyrrole dione to the alkenyl succinate is 5:1~20:1, for example, 5:1, 7:1, 10:1, 12:1, 15:1, 18:1 or 20:1.

[0057] In a preferred embodiment of the present invention, the anti-wear agent includes one or more of molybdenum disulfide, molybdenum dialkyl dithiophosphate or molybdenum amine ester compounds.

[0058] Among them, the molybdenum disulfide is a solid lubricant, which can be dispersed in the grease to form a colloidal state and has weak alkalinity; wherein the dialkyl dithiophosphate molybdenum and molybdenum amine ester compounds will decompose into molybdenum disulfide, sulfide, phosphide and nitride under high load pressure conditions, and these products are dispersed in the grease, adsorbed and deposited on the friction surface, and the molybdenum disulfide forms a protective film covering the anti-wear layer, thereby playing a role in friction reduction, anti-wear and lubrication.

[0059] In the present invention, the anti-wear agent is, for example, molybdenum disulfide, molybdenum dialkyl dithiophosphate, molybdenum amine ester compound, molybdenum disulfide and molybdenum dialkyl dithiophosphate, molybdenum disulfide and molybdenum amine ester compound, molybdenum dialkyl dithiophosphate and molybdenum amine ester compound, or a combination of molybdenum disulfide, molybdenum dialkyl dithiophosphate and molybdenum amine ester compound.

[0060] In a preferred embodiment of the present invention, the antiwear agent comprises:

[0061] Molybdenum disulfide 5~10 parts

[0062] 1 to 3 parts of dialkyl dithiophosphate molybdenum, and

[0063] 1-3 parts of molybdenum amine ester compound.

[0064] Specifically, molybdenum disulfide particles will be suspended in the base grease, affecting its lubrication performance. To alleviate this problem, the anti-wear agent of the preferred embodiment of the present invention also includes dialkyl dithiophosphate molybdenum and molybdenum amine ester compounds. However, the dialkyl dithiophosphate molybdenum and molybdenum amine ester compounds are easily oxidized and decomposed into acidic substances under high temperature and high pressure conditions, which will destroy the soap fiber structure of the grease, and it is not advisable to add too much.

[0065] Preferably, the weight ratio of the molybdenum disulfide, the molybdenum dialkyl dithiophosphate and the molybdenum amine ester compound is 4:1:1.

[0066] In a preferred embodiment of the present invention, the particle size of the molybdenum disulfide is 30-50 nanometers, and the friction coefficient is 0.04-0.06.

[0067] Further preferably, the molybdenum disulfide is an inorganic fullerene-structured nanoparticle, which is a non-polar spherical structure composed of 60 molybdenum disulfide molecules and has a particle size of 40 nanometers.

[0068] In a preferred embodiment of the present invention, the antioxidant comprises an amine compound and / or a phenol compound, for example, an amine compound, a phenol compound or a combination of an amine compound and a phenol compound.

[0069] Among them, the phenolic compound is suitable for neutral and alkaline greases, the phenolic compound is suitable for acidic greases, and the amine compound and the phenolic compound are used in combination. When the grease is oxidized to produce acid and gradually becomes neutral and acidic, the phenolic compound can play an antioxidant role.

[0070] Preferably, the antioxidant comprises amine compounds and phenolic compounds.

[0071] The second object of the present invention is to provide a method for preparing grease, which comprises the following steps: mixing the composite titanium-based grease and the composite lithium-based grease, adding the rust inhibitor, anti-wear agent and antioxidant, mixing, heating and stirring, and then grinding.

[0072] Specifically, the composite titanium-based grease and the composite lithium-based grease are stirred and mixed in a reaction kettle.

[0073] In a preferred embodiment of the present invention, after the composite titanium-based grease and the composite lithium-based grease are mixed, the pyrrolopyrrole dione, alkenyl succinate, molybdenum disulfide, dialkyl dithiophosphate molybdenum, molybdenum amine ester compound, amine compound and phenolic compound are added in sequence, mixed, then heated and stirred, and then ground.

[0074] Specifically, each time a material is added, it is stirred and mixed thoroughly before adding the next material.

[0075] In a preferred embodiment of the present invention, the heating temperature is 90° C. to 110° C., the stirring speed is 1000 to 1100 r / min, and the stirring time is 1.5 to 2.5 h.

[0076] Preferably, the heating temperature is 100° C., the stirring speed is 1000 r / min, and the stirring time is 2 h.

[0077] In a preferred embodiment of the present invention, the grinding times is 3 to 5 times.

[0078] Preferably, the grease is finely ground on a calendering grinder for four times, and after grinding, the obtained grease is tested, and after passing the test, it is filled.

[0079] A third object of the present invention is to provide a use of the grease as described above, which is used to lubricate the bearings of the annealing furnace fan.

[0080] Example

[0081] In the following examples, unless otherwise specified, all raw materials are commercially available products.

[0082] The raw materials are as follows:

[0083] 1. Composite titanium-based grease

[0084] 2. Complex lithium-based grease: Comparative Examples 2 and 10 do not use complex lithium-based grease.

[0085] 3. Rust inhibitor: The rust inhibitors in Examples 1 to 9 are pyrrolopyrrole dione and alkenyl succinate, the rust inhibitor in Example 10 is pyrrolopyrrole dione and dodecenyl succinic acid, the weight ratio of pyrrolopyrrole dione and alkenyl succinate in Examples 1 to 6 is 10:1, the weight ratio of pyrrolopyrrole dione and alkenyl succinate in Example 7 is 5:1, the weight ratio of pyrrolopyrrole dione and alkenyl succinate in Example 8 is 20:1, the weight ratio of pyrrolopyrrole dione and alkenyl succinate in Example 9 is 4:1, and the weight ratio of pyrrolopyrrole dione and dodecenyl succinic acid in Example 10 is 10:1. The rust inhibitor in Comparative Example 3 is lanolin.

[0086] 4. Antiwear agent: The antiwear agent in Examples 1 to 3 and Examples 6 to 10 is molybdenum disulfide, molybdenum dialkyl dithiophosphate and molybdenum amine ester compound, and the weight ratio of the three is 4:1:1. The antiwear agent in Example 4 is molybdenum disulfide and molybdenum dialkyl dithiophosphate, and the antiwear agent in Example 5 is molybdenum disulfide and molybdenum amine ester compound. The antiwear agent in Comparative Example 4 is borate.

[0087] 5. Antioxidant: The antioxidants in Examples 1 to 4 and Examples 7 to 10 are amine compounds and phenolic compounds, and the weight ratio between the two is 1:1. The antioxidant in Example 5 is an amine compound, and the antioxidant in Example 6 is a phenolic compound. The antioxidant in Comparative Example 5 is a thioester compound.

[0088] The preparation method of the grease comprises the following steps:

[0089] Step 1: Stir and mix the composite titanium-based grease and the composite lithium-based grease in a reaction kettle.

[0090] Step 2: sequentially stir and mix the rust inhibitor, anti-wear agent, antioxidant and the mixture obtained in step 1 evenly.

[0091] Step 3: Heat and stir the mixture obtained in step 2 to obtain grease; the heating temperature is 100° C., the stirrer speed is 1000 r / min, and the stirring time is 2 h.

[0092] Step 4: Finely grind the grease 4 times on a calender grinder.

[0093] Step 5: Test the grease obtained in step 4.

[0094] The raw material ratios of Examples 1 to 10 are shown in Table 1, and the raw material ratios of Comparative Examples 1 to 10 are shown in Table 2.

[0095] Table 1 Ratio of raw materials in Examples 1 to 10

[0096]

[0097] Table 2 Raw material ratios of comparative examples 1 to 10

[0098]

[0099] Performance Testing

[0100] The lubricating greases prepared in Examples 1 to 10, the lubricating greases prepared in Comparative Examples 1 to 10, and the overseas brand 1250 were subjected to performance tests, and the test items and test methods are as follows:

[0101] 1. Cone penetration (0.1mm) GB / T269

[0102] 2. Dropping point (℃) GB / T4929

[0103] 3. Four-ball machine load PD value (kgf) (gradually increase the load at a certain temperature and speed) SH / T0202

[0104] 4. Corrosion (T2 copper sheet, 100°C, 24h) SH / T0331

[0105] 5. Corrosion (steel sheet, 100°C, 24h) SH / T0331

[0106] 6. Steel mesh oil separation (100℃, 24h) %SH / T0324

[0107] 7. Water resistance (38°C, 1h) SH / T0109

[0108] 8. Four-ball machine load PB value (kgf) SH / T0202

[0109] 9. Four-ball machine load ZMZ value (kgf) SH / T0202

[0110] The test results are shown in Table 3:

[0111] Table 3 Test results

[0112] project Cone penetration (0.1mm) Dropping point (℃) PD value (kgf) Corrosion (T2 copper sheet, 100℃, 24h) Corrosion (steel sheet, 100℃, 24h) Steel mesh oil separation (100℃, 24h, %) Water resistance (38℃, 1h) PB value (kgf) ZMZ value (kgf) Example 1 260 319 450 1a 1a 1.1 0.8 155 100 Example 2 245 305 420 1a 1a 0.7 0.3 153 105 Example 3 250 320 600 1a 1a 0.3 0.2 160 120 Example 4 253 315 550 1a 1a 0.4 0.25 159 117 Example 5 258 312 460 1a 1a 1.2 0.7 157 108 Example 6 246 306 400 1a 1a 1.5 0.4 150 103 Example 7 251 314 560 1a 1a 0.9 0.5 151 101 Example 8 253 316 552 1a 1a 1.1 0.9 154 106 Example 9 252 319 570 1a 1a 0.8 0.7 157 102 Example 10 259 301 543 1a 1a 1.3 1.1 150 100 Comparative Example 1 317 300 308 1a 1a 1.8 2.1 100 85 Comparative Example 2 316 270 310 1a 1a 1.7 0.6 110 90 Comparative Example 3 253 310 508 1b 1b 0.7 0.8 149 110 Comparative Example 4 254 295 485 1a 1a 2.5 1.5 130 108 Comparative Example 5 249 317 310 1b 1b 2.1 0.75 90 100 Comparative Example 6 270 290 315 1a 1a 1.8 2.5 75 80 Comparative Example 7 240 286 420 1a 1a 1.5 3.1 78 120 Comparative Example 8 258 265 300 1b 1b 1.7 1.8 86 95 Comparative Example 9 263 270 330 1b 1b 2.2 3.5 90 85 Comparative Example 10 255 268 505 1a 1a 1.9 1.7 97 110 Overseas brands 1250 265 280 320 1b 1b 2 3 80 52

[0113] From the table above we can see that:

[0114] The composite titanium-based grease and the composite lithium-based grease provided by the present invention work together to make the soap fiber structure more stable, which is conducive to improving the dropping point of the grease, so that the dropping point of the grease is as high as 320°C, the oil film strength is high, the shear stability of the grease is improved, and the four-ball machine load PD value of the grease is as high as 600kgf, which can enhance the binding ability of the base oil and improve the water-resistant performance of the grease, thereby extending the service life of the grease. Even under continuous high-humidity working conditions, it is not easy to emulsify and thin, thereby solving the problem that the overseas brand 1250 grease is easy to thin and lose quickly and has a short greasing cycle.

[0115] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the present application.

Claims

1. A lubricating grease, characterized in that: The invention comprises the following raw materials in parts by weight: 75~80 parts of composite titanium-based grease 15~20 parts of lithium complex grease Rust inhibitor 2.1~6 parts 7~16 parts of anti-wear agent, and 1~4 parts of antioxidant; The weight ratio of the composite titanium-based grease to the composite lithium-based grease is 4-5:1; The composite lithium-based grease is mainly made of hydroxy fatty acid, low molecular weight acid lithium salt and base oil; The rust inhibitor comprises dione pyrrolopyrrole and alkenyl succinate, and the weight ratio of the dione pyrrolopyrrole to the alkenyl succinate is 5 to 20:1; The anti-wear agent comprises: Molybdenum disulfide 5~10 parts 1-3 parts of dialkyl dithiophosphate molybdenum, and 1-3 parts of molybdenum amine ester compound; The weight ratio of the molybdenum disulfide, the molybdenum dialkyl dithiophosphate and the molybdenum amine ester compound is 4:1:1; The molybdenum disulfide is an inorganic fullerene-structured nanoparticle, which is a non-polar spherical structure composed of 60 molybdenum disulfide molecules, has a particle size of 40 nanometers, and a molybdenum friction coefficient of 0.04-0.

06.

2. The lubricating grease according to claim 1, characterized in that: The antioxidant includes amine compounds and / or phenolic compounds.

3. A method for preparing the lubricating grease according to any one of claims 1 to 2, characterized in that: The preparation method comprises the following steps: after mixing the composite titanium-based grease and the composite lithium-based grease, adding the rust inhibitor, anti-wear agent and antioxidant, mixing, heating and stirring, and then grinding.

4. A use of the lubricating grease according to any one of claims 1 to 2, characterized in that: The grease is used to lubricate the annealing furnace fan bearing.

Citation Information

Patent Citations

  • Self-repairing compound titanium-based grease and preparation method thereof

    CN103160369A

  • Lithium base grease used for RV decelerators, and preparation method thereof

    CN105524687A

  • Lubricating grease composition

    US20070129267A1